Dual-Disturbance Observers-based Control of UAV Subject to Internal and External Disturbances - Guo, Kexin; Jia, Jindou; Yu, Xiang; Guo, Lei (Chinese Automation Congress (Online), 2019)
This paper presents an embedded micro loop to enhance the anti-disturbance performance for unmanned aerial vehicles (UAVs). The UAV dynamics can be represented by the Lagrange-Euler formalism. The proposed control scheme, known as composite hierarchical anti-disturbance control (CHADC), consists of nonlinear disturbance observer (NDO) and the control law. Two NDOs are designed in translation loop and stabilization loop, respectively, to estimate their corresponding disturbances. It should be mentioned that the control portion in this paper can be generated by any control design approaches. Experimental results in the presence of wind disturbance, motors' faults, and hybrid disturbances illustrate the robustness and effectiveness of the proposed method when comparing to the classical method.